Clinical characteristics and management status of Turner syndrome in 1 089 children - Liang, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To investigate the clinical characteristics and management status of children with Turner syndrome (TS) in China. Methods: As a cross-sectional study, 1 089 TS patients were included in the database of the National Collaborative Alliance for the Diagnosis and Treatment of Turner Syndrome from August 2019 to November 2023. Clinical characteristics (growth development, sexual development, organ anomalies, etc.), karyotypes, auxiliary examinations, and treatments were collected and analyzed. Results: Among the 1 089 TS cases, 809 were recorded karyotypes. The karyotype distribution was as follows: 45, X in 317 cases (39.2%), X chromosome structural variants (including partial deletions of p or q arm, ring chromosome, and marker chromosome) in 89 cases (11.0%), 45, X/46, XX mosaicism in 158 cases (19.5%), mosaicism with X chromosome structural variants in 209 cases (25.8%), and presence of Y chromosome material in 36 cases (4.4%). Among the 824 TS cases, the age of diagnosis was 9.7(6.4, 12.2) years, with a height standard deviation score (HtSDS) of -3.1±1.2. Five hundred and fifty three cases underwent growth hormone (GH) stimulation test, and 352 cases (63.7%) had GH peak values <10 μg/L and 75.9% (577/760) had low IGF1 levels, with IGF1 SDS ≤-2 accounting for 38.2% (290 cases). Among 471 cases aged ≥8 years, 132 cases (28.0%) showed spontaneous sexual development (mean bone age (11.0±1.7) years), 10 cases had spontaneous menarche (mean bone age (12.0±2.2) years), and 2 cases had regular menstrual cycles. Common physical features included cubitus valgus (311 cases (28.5%)), neck webbing (188 cases (17.2%)), low posterior hairline (185 cases (17.0%)), shield chest (153 cases (14.0%)), high arched palate (127 cases (11.6%)), short fourth metacarpal (43 cases (3.9%)), and spinal abnormalities (38 cases (3.5%)). Congenital cardiovascular and urogenital anomalies occurred in 91 cases (19.4%) and 66 cases (12.0%)respectively. Abdominal ultrasound in 33 cases (7.2%) indicated fatty liver, hepatomegaly, intrahepatic bile duct stones, and splenomegaly. Among 23 cases undergoing oral glucose tolerance test (OGTT) test, 2 were diagnosed with diabetes mellitus and 4 with impaired glucose tolerance. Following diagnosis, 669 cases (80.7%) received rhGH treatment at a chronological age of (9±4) years and bone age of (8.3±3.2) years. Additionally, 112 cases (19.4%) received sex hormone replacement therapy starting at the age of (14±4) years and bone age of (12.6±1.2) years. Conclusions: The karyotypes of 45, X and mosaicism were most common in Chinese children with TS. The clinical manifestations were mainly short stature and gonadal dysplasia. However, a few TS children could be in the normal range of height, and some cases among those aged of ≥8 years old had spontaneous sexual development. Some exhibited physical features, congenital cardiovascular and urogenital anomalies, and dysfunction of the hypothalamic-pituitary-IGF1 axis. Moreover, a few of them developed impaired glucose tolerance and diabetes mellitus. Following diagnosis, most of the patients received rhGH treatment, and a few of them received sex hormone replacement therapy